2017
DOI: 10.1002/adma.201701475
|View full text |Cite
|
Sign up to set email alerts
|

Giant Ferroelectric Polarization in Ultrathin Ferroelectrics via Boundary‐Condition Engineering

Abstract: Tailoring and enhancing the functional properties of materials at reduced dimension is critical for continuous advancement of modern electronic devices. Here, the discovery of local surface induced giant spontaneous polarization in ultrathin BiFeO ferroelectric films is reported. Using aberration-corrected scanning transmission electron microscopy, it is found that the spontaneous polarization in a 2 nm-thick ultrathin BiFeO film is abnormally increased up to ≈90-100 µC cm in the out-of-plane direction and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 43 publications
1
36
0
Order By: Relevance
“…1c, the high-angle XRD θ−2θ scan exhibits only (00 l) peaks yielding an out-of-plane (OOP) lattice parameter c = 4.67 Å. The broad peak at 30.4°has been suggested to be a tetragonal β-Bi 2 O 3 phase, which can impose a net compressive strain on BFO and thus stabilize the T' phase (without forming relaxed R' phase striations) at thicknesses well over 60 nm 45,49 . High-angle annular dark field (HAADF) scanning transmission electron microscopy (STEM) was used to study the defect structure in these samples at the atomic scale ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1c, the high-angle XRD θ−2θ scan exhibits only (00 l) peaks yielding an out-of-plane (OOP) lattice parameter c = 4.67 Å. The broad peak at 30.4°has been suggested to be a tetragonal β-Bi 2 O 3 phase, which can impose a net compressive strain on BFO and thus stabilize the T' phase (without forming relaxed R' phase striations) at thicknesses well over 60 nm 45,49 . High-angle annular dark field (HAADF) scanning transmission electron microscopy (STEM) was used to study the defect structure in these samples at the atomic scale ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This effect is ascribed to the presence of a strain-stabilizing Bi 2 O 3 phase. 35,40 More specifically, it has recently been found that fine tuning of growth conditions can favour the formation of "stacking fault" like nanoregions in our T films: these regions appear to help maintain the strain required for T BFO up to larger thicknesses. To determine the structural symmetry, XRD RSMs around the (103) and (113) reflections [Figs.…”
Section: © 2018 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%
“…On the other hand, recent observation of a strong interaction between ferroelectric polarization and built-in fields induced by charged impurity defects embedded in the ferroelectric matrix suggests that these defects may be used as nano-building-blocks that can provide a strong electrostatic driven force for stabilization of complex domain structures 13,14 . For example, it has been shown that nanoscale planar charged defects in BiFeO 3 thin films can induce novel head-tohead mixed-phase polarization structures 13 .…”
mentioning
confidence: 99%